Tirzas pagasta avotu un Pierīgas avotu ķīmiskās un bioloģiskās kvalitātes salīdzinājums - Isidorova, Anastasija (Latvijas Universitāte, 2010)
Bakalaura darba mērķis ir novērtēt Tirzas pagasta un Pierīgas avotu ķīmisko un bioloģisko kvalitāti. Avotu ķīmiskās un bioloģiskās kvalitāte novērtēšanai tika veiktas avotu ūdeņu ķīmiskās un bakterioloģiskās analīzes. Avotu ūdens ķīmiskais sastāvs tika novērtēts pēc MK noteikumos Nr.235 noteiktās elementu robežkoncentrācijas un salīdzināts ar pārdošanā esošo galda un minerālūdeni. Avotu ūdens bakterioloģiskā kvalitāte tika novērtēta pēc MK noteikumos Nr.634 noteiktajām alohtonās un autohtonās mikrofloras robežkoncentrācijām avotu ūdeņiem. Atslēgas vārdi: avots, Tirzas pagasts, Ķekavas avots, Sauriešu avots, avotu ūdens kvalitāte.

The title of the Bachelor thesis is „Comparison of chemical and biological quality of springs water in Tirza rural municipality and Riga suburbs”. The aim of the thesis is to determine water quality of springs in Tirza rural municipality and Riga suburbs, and find out if there are contamination problems. Chemical and bacteriological analysis was carried out to determine water quality. Chemical composition was evaluated as provided by Cabinet of Ministers regulation No 235, which specifies maximum permissible value of elements in drinking water. Bacteriological analysis was evaluated as provided by Cabinet of Ministers regulation No 634, which specifies maximum permissible quantities of revivable colonies of micro-organisms at the place of abstraction and in pre-packed natural mineral water or spring water. Key words: spring, Tirza, Kekava spring, Sauriesi spring, spring water quality.
Comparison of chemical and biological quality of springs waters in Tirza rural municipality and Riga suburbs
Keywords: Vides zinātne